Prenatally diagnosed single umbilical artery: The role and relationship of additional risk factors in the fetus for congenital heart disease. Issue 2 (14th July 2015) - Chen, Kai; Akoma, Ugochi; Anderson, Andrea; Mertz, Heather; Quartermain, Michael D.
ABSTRACT: Purpose: Single umbilical artery (SUA) has been associated with an increased risk of congenital heart disease (CHD). Women carrying fetuses with an SUA are often referred for fetal echocardiography, but data to support the need for this testing remain controversial. Methods: A retrospective review of the records for all women carrying fetuses with an SUA who had undergone fetal echocardiography between 2009 and 2012 at our center was performed. Data on the maternal and fetal risk factors for CHD were collected, and the fetuses were categorized into three groups: low risk (LR; an SUA with no additional risk factors for CHD), moderate risk (MR; an SUA with one additional risk factor for CHD), and high risk (HR; an SUA with two or more additional risk factors for CHD). Results: In total, 101 such patients were identified: 69 LR, 26 MR, and 6 HR. No fetuses in the LR group, three in the MR group, and two in the HR group had CHD ( p  = 0.0005). Conclusions: An SUA in an LR fetus did not increase the risk of CHD in our cohort, whereas an SUA in the presence of additional risk factors was associated with significantly increased risk for CHD. Our results suggest that referral for a fetal echocardiogram is indicated for women carrying fetuses with an SUA when additional risk factors for CHD are present. In an LR fetus with an SUA, however, echocardiography may not provide additional benefit unless CHD is suggested on screening obstetric sonography. © 2015 Wiley Periodicals, Inc. J Clin Ultrasound 44 :113–117, 2016